The Influence of Service Quality on Satisfaction Level and Company Image Using Smart Electricity Based on Household Segment - Siregar, Wilfrid Sahat P; Mahrinasari, Mahrinasari; Panjaitan, Dorothy R (Budapest International Research and Critics University, 2022)
Electricity is one of the important needs that people use to complete a job or daily activity. Prepaid electricity is one of the innovations in improving the quality of service for customers so that customers are satisfied and maintain the company's image. However, the problem in the field is that not all electricity customers use prepaid electricity innovation. The purpose of this study is to analyze whether service quality has an effect on customer satisfaction and corporate image.The research was conducted at PLN UP3 Kotabumi with 300 customers as respondents. The data analysis method used is pThis research is path analysis. The results showed that simultaneously service quality had a significant effect on customer satisfaction and corporate image. Service quality which includes tangibles, responsiveness, assurance variables have a direct significant effect on customer satisfaction while reliability and empathy have no significant effect on customer satisfaction. Service quality on the assurance variable has a direct significant effect oncompany image.